2009
DOI: 10.1128/mcb.01337-08
|View full text |Cite
|
Sign up to set email alerts
|

APE1/Ref-1 Interacts with NPM1 within Nucleoli and Plays a Role in the rRNA Quality Control Process

Abstract: APE1/Ref-1 (hereafter, APE1), a DNA repair enzyme and a transcriptional coactivator, is a vital protein in mammals. Its role in controlling cell growth and the molecular mechanisms that fine-tune its different cellular functions are still not known. By an unbiased proteomic approach, we have identified and characterized several novel APE1 partners which, unexpectedly, include a number of proteins involved in ribosome biogenesis and RNA processing. In particular, a novel interaction between nucleophosmin (NPM1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
411
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(436 citation statements)
references
References 64 publications
(104 reference statements)
19
411
3
Order By: Relevance
“…Thirdly, under the model outlined above, NPM1 is expected to act as a negative regulator of APE1. However, studies have instead observed that, in vitro, NPM1 binding to APE1 enhances its AP-endonuclease activity (Vascotto et al 2009) lysates, despite no longer being sequestered in nucleoli (Vascotto et al 2014). NPM1 -/-cells also showed an increased sensitivity to BER-inducing agents such as H 2 O 2 , KBrO 3 and MMS, and carried a greater number of AP-sites compared to NPM1 +/+ cells, suggesting that NPM1 is in fact required for APE1 function in vivo (Vascotto et al 2014).…”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirdly, under the model outlined above, NPM1 is expected to act as a negative regulator of APE1. However, studies have instead observed that, in vitro, NPM1 binding to APE1 enhances its AP-endonuclease activity (Vascotto et al 2009) lysates, despite no longer being sequestered in nucleoli (Vascotto et al 2014). NPM1 -/-cells also showed an increased sensitivity to BER-inducing agents such as H 2 O 2 , KBrO 3 and MMS, and carried a greater number of AP-sites compared to NPM1 +/+ cells, suggesting that NPM1 is in fact required for APE1 function in vivo (Vascotto et al 2014).…”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%
“…The first is that, while APE1 is enriched in the nucleoli, extensive nucleoplasmic APE1 staining is still observed in most cells, suggesting that NPM1 sequesters only a relatively minor pool (an estimated 5-10% of total cellular APE1) into nucleoli (Lirussi et al 2012;Vascotto et al 2009). …”
Section: Holding Out: Ncl Sequesters Rpa Away From the Replication Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous flow cytometric studies have indicated that the effect of APE1 siRNA on cisplatin sensitivity may be partly due to the modulation of the cell cycle, as a result of cellular response to DNA damage. New data demonstrate that APE1 affects cell growth by directly acting on RNA quality control mechanisms, thus affecting gene expression through post-transcriptional mechanisms (32). Future research is necessary in this area to identify the relationship between APE1 and cell cycle.…”
Section: Cell Cycle Perturbations Aftermentioning
confidence: 99%